Bioabsorbable sealing powder
Patent Information
- Application Number
- CN202280009368.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-01-08
- Filing Date
- 2022-01-03
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-01-03
AI Technical Summary
尽管此类材料经由物理吸附来浓缩血液和经血产物,但是它们不被身体吸收,并且在移除时,凝块可能被移除,导致进一步出血
[0201] The advantage of using a fibrous carrier structure in the hemostatic sheet of the present invention is that the sealing powder can be uniformly distributed throughout the carrier structure without difficulty. Such uniform distribution is difficult to achieve, for example, in a foamed carrier structure.
Smart Images

Figure BDA0004326544790000301 
Figure BDA0004326544790000381
Abstract
Description
Technical Field
[0001] This invention relates to a bioabsorbable sealing powder, which comprises:
[0002] (a) A water-soluble electrophilic polymer carrying at least three reactive electrophilic groups, which are capable of reacting with amine groups to form covalent bonds;
[0003] (b) A water-soluble nucleophilic crosslinking agent carrying at least two reactive nucleophilic groups, which are capable of reacting with reactive electrophilic groups of an electrophilic polymer in the presence of water to form a covalent bond between the electrophilic polymer and the nucleophilic crosslinking agent;
[0004] (c) Water-absorbing particles containing at least 50% by weight of a water-insoluble polymer, the water-insoluble polymer containing a reactive nucleophilic group selected from amine groups and thiol groups;
[0005] (d) A water-soluble dispersant that is a solid at 20°C, wherein the water-soluble dispersant is selected from monosaccharides, disaccharides, oligosaccharides, sugar alcohols, and combinations thereof;
[0006] Components (a), (b), (c) and (d) may be contained in the same particles or in different particles.
[0007] When the sealing powder of this invention is applied to wet tissue, the reactive components in the powder react rapidly to form a tissue-adhesive hydrogel, which seals the underlying tissue. The adhesive hydrogel provides a sufficiently strong seal to effectively seal against pulmonary air leaks. Background Technology
[0008] Hemostasis is a tightly regulated process that maintains blood flow through the vascular system while simultaneously responding to thrombotic reactions to tissue damage. Maintaining hemostasis requires complex interactions between the vessel walls, platelets, and the coagulation and fibrinolytic systems. Hemostasis has two main phases: a primary phase (i.e., the cellular phase) and a secondary phase (i.e., the humoral phase).
[0009] Primary hemostasis begins immediately after endothelial rupture and is characterized by vasoconstriction, platelet adhesion, and the formation of soft emboli. Following injury, temporary local contraction of vascular smooth muscle slows blood flow, promoting platelet adhesion and activation. Within 20 seconds of injury, circulating von Willebrand factor attaches to the subendothelial membrane at the site of injury and to glycoproteins on the platelet surface. As platelets adhere to the injury surface, they are activated by contact with collagen-exposed receptors that bind circulating fibrinogen, forming soft emboli composed of aggregated platelets and fibrinogen. This hemostatic phase is brief, and the soft emboli can be easily sheared off the injury surface.
[0010] During secondary hemostasis, the soft platelet embolism is stabilized to form a clot. At the onset of the coagulation cascade, vasoconstriction and the resulting reduction in blood flow are maintained by platelet secretion of serotonin, prostaglandins, and thromboxane. The coagulation cascade is a series of platelet-dependent reactions involving several plasma proteins, calcium ions, and platelets, leading to the conversion of fibrinogen to fibrin. Coagulation factors are produced by the liver and circulate in inactive forms until the coagulation cascade begins. Each step of the cascade is then initiated and completed via a series of successive and dependent activation reactions of coagulation factors. In the final step, thrombin converts the soluble plasma protein fibrinogen to the insoluble protein fibrin, while simultaneously converting factor XIII to factor XIIIa. This factor conversion stabilizes fibrin and leads to the cross-linking of fibrin monomers, resulting in a stable clot.
[0011] During surgery, it is crucial to maintain a delicate balance between bleeding and clotting, ensuring continued blood flow to the surgical site without excessive blood loss to optimize surgical success and patient outcomes. Continuous bleeding from diffusing capillaries or venules during surgery can mask the surgical area, prolong the procedure, increase the risk of physiological complications, and expose the patient to transfusion-related risks.
[0012] Surgeons have a range of options for controlling bleeding, including mechanical and thermal techniques and devices, as well as drug therapy and topical agents.
[0013] One of the earliest topical hemostatic agents was cotton in the form of gauze sponges. Although such materials concentrate blood and menstrual products through physical absorption, they are not absorbed by the body, and upon removal, clots may be removed, leading to further bleeding. Absorbable topical hemostatic agents have been developed and provide useful adjunctive treatment when conventional hemostasis methods are ineffective or impractical. Topical hemostatic agents can be applied directly to the bleeding site and prevent continuous bleeding. Hemostasis using topical agents also avoids the adverse effects of systemic hemostatic drugs, such as unwanted blood clots. Furthermore, in surgical procedures where blood loss is unpredictable, small amounts of topical hemostatic agents can be used when blood loss is minimal, and more extensively during periods of severe bleeding.
[0014] Many topical hemostatic agents are currently available for use in surgical procedures. They can be divided into two categories: those that provide their mechanism of action on the coagulation cascade in a biologically active manner, and those that are activated by contact and promote platelet aggregation. Passive topical hemostatic agents include collagen, cellulose, and gelatin, while active agents include thrombin and products in which thrombin is combined with passive agents to provide an overall active product.
[0015] US 2003 / 0064109 describes a dry hemostatic powder prepared by a method comprising the following steps: providing an aqueous solution comprising gelatin in combination with at least one rehydration aid; drying the solution to produce a solid; grinding the solid to produce a powder; crosslinking the powder; removing at least 50% (w / w) of the rehydration aid; and drying the crosslinked gelatin to produce a powder. The rehydration aid may include at least one material selected from polyethylene glycol (PEG), polyvinylpyrrolidone (PVP), and dextran.
[0016] US 2012 / 0021058 describes a method for preparing a hemostatic composition, the method comprising: a) providing a dry particulate formulation of a biocompatible polymer; and b) coating the particles in the dry particulate formulation with a coagulation inducing agent formulation (such as a thrombin solution). The biocompatible polymer may be selected from gelatin, soluble collagen, albumin, hemoglobin, fibrinogen, fibrin, casein, fibronectin, elastin, keratin, laminin, and derivatives or combinations thereof.
[0017] US 2013 / 0316974 describes a hemostatic material comprising compacted ORC powder containing particles having an average aspect ratio of about 1 to about 18. The hemostatic material may also contain additives selected from polysaccharides, calcium salts, anti-infective agents, hemostatic agents, gelatin, and collagen.
[0018] US 2016 / 0271228 describes a hemostatic composition comprising:
[0019] ● Particulate hemostatic biocompatible polymers, selected from proteins, polysaccharides, biopolymers, non-biopolymers, and their derivatives and combinations, wherein the particulate hemostatic biocompatible polymers exist as granular particles with a median diameter ranging from 50 μm to 700 μm.
[0020] ● A hydrophilic crosslinking agent comprising electrophilic reactive groups, wherein the electrophilic reactive groups retain their reactivity until the composition is exposed to a patient's blood pressure, wherein the electrophilic reactive groups are configured to crosslink with the patient's blood proteins to form a gel with sealing and hemostatic properties; and
[0021] ● An adhesive that does not react with the electrophilic reactive groups of the hydrophilic crosslinking agent; wherein the hemostatic composition is in paste form.
[0022] WO 2012 / 057628 describes a kit for producing a biocompatible crosslinking polymer, the kit comprising an electrophilically activated polyoxazoline (EL-POx), the EL-POx comprising m electrophilic groups; and the nucleophilic crosslinking agent comprising n nucleophilic groups, wherein the m electrophilic groups are capable of reacting with the n nucleophilic groups to form covalent bonds; wherein m>2, n>2 and m+n>5; and wherein at least one of the m electrophilic groups is an electrophilic side group.
[0023] WO 2016 / 056901 describes an adhesive hemostatic product selected from coating mesh, coating foam, or coating powder, the hemostatic product comprising:
[0024] ● A porous solid substrate having a porosity of at least 5% by volume and including an outer surface comprising a nucleophilic polymer containing reactive nucleophilic groups;
[0025] ● An adhesive coating covering at least a portion of a solid substrate, the coating comprising an electrophilically activated polyoxazoline (EL-POX), the EL-POX containing on average at least one reactive electrophilic group.
[0026] US 2016 / 0375202 describes an apparatus for extruding hemostatic powder, the apparatus comprising:
[0027] a) An elongated hollow reservoir having a manual air pump attached to the reservoir and an extrusion port at the distal end of the reservoir.
[0028] b) A porous filter, which is slidably disposed within the reservoir and between the air pump and the extrusion port;
[0029] c) A spring disposed within the reservoir, between the air pump and the filter;
[0030] The powder is disposed within the reservoir, between the filter and the extrusion port, and the pump is in fluid communication with the extrusion port through the porous filter and the powder. Summary of the Invention
[0031] The inventors have developed a bioabsorbable sealing powder that can be conveniently used to control bleeding and / or provide a protective seal during surgery.
[0032] The sealing powder of the present invention comprises:
[0033] (a) at least 5% by weight of a water-soluble electrophilic polymer carrying at least 3 reactive electrophilic groups, wherein the reactive electrophilic groups are capable of reacting with amine groups to form covalent bonds;
[0034] (b) 1% to 50% by weight of a water-soluble nucleophilic crosslinker carrying at least two reactive nucleophilic groups, which are capable of reacting with reactive electrophilic groups of an electrophilic polymer in the presence of water to form a covalent bond between the electrophilic polymer and the nucleophilic crosslinker;
[0035] (c) 1% to 60% by weight of absorbent particles, the absorbent particles containing at least 50% by weight of a water-insoluble polymer, the water-insoluble polymer containing a reactive nucleophilic group selected from amine groups, thiol groups and combinations thereof.
[0036] (d) 10% to 75% by weight of a water-soluble dispersant that is a solid at 20°C, wherein the water-soluble dispersant is selected from monosaccharides, disaccharides, oligosaccharides, sugar alcohols, and combinations thereof;
[0037] The combination of components (a), (b), (c) and (d) accounts for at least 60% by weight of the sealing powder;
[0038] The sealing powder has a tap density in the range of 0.3 g / ml to 0.9 g / ml;
[0039] At least 90% by weight of the powder has a diameter of less than 600 μm, and no more than 10% by weight of the powder has a diameter of less than 10 μm; and
[0040] Components (a), (b), (c) and (d) may be contained in the same particles or in different particles.
[0041] When applied to wet tissue, the sealing powder of the present invention rapidly forms a hydrogel-like seal that adheres to the tissue. The sealing powder can be suitably used to provide an effective seal for, for example, pulmonary air leaks. Additionally, the sealing powder exhibits excellent hemostatic properties because it can absorb large amounts of blood, forming a strong gel-like clot that seals the bleeding site.
[0042] The sealing powder of this invention can be easily distributed on tissue. If necessary, additional sealing powder can be applied to form an additional sealing layer that adheres to the underlying hydrogel.
[0043] While the inventors do not wish to be bound by theory, it is believed that when a layer of hemostatic powder is applied to wet tissue, both the water-soluble electrophilic polymer and the water-soluble nucleophilic polymer dissolve rapidly. The dissolved electrophilic polymer reacts with the reactive nucleophilic groups of the dissolved water-soluble nucleophilic polymer to form a hydrogel containing water-absorbing particles. These water-absorbing particles provide hygroscopic capacity due to their swelling ability. The dissolved electrophilic polymer also reacts with proteins in the tissue, thereby fixing the hydrogel to the tissue. Furthermore, the dissolved electrophilic polymer reacts with proteins in the blood, thereby producing a gelled blood clot.
[0044] The water-soluble dispersant in the sealing powder of the present invention ensures that the other components of the sealing powder are rapidly and uniformly dispersed when the sealing powder comes into contact with moisture. Furthermore, the inclusion of a water-soluble dispersant enables the preparation of a sealing powder composed of particles with a sufficiently high density to allow for precise application of the powder to tissues using an airflow (e.g., an airflow generated by a bellows).
[0045] Surprisingly, after the sealing powder is applied to the wet tissue, it can be properly squeezed with a saline-soaked wet gauze pad, as the gauze pad does not stick to the gelled / gelled sealing powder.
[0046] Another aspect of the present invention relates to a method for preparing the bioabsorbable sealing powder of the present invention, the method comprising the following steps:
[0047] (a) Provide particles A comprising an electrophilic polymer and a water-soluble dispersant;
[0048] (b) Provide particles B comprising a nucleophilic crosslinking agent, water-absorbing particles and a water-soluble dispersant;
[0049] (c) Combine particle A and particle B.
[0050] Another aspect of the present invention relates to an apparatus for powder application, the apparatus comprising:
[0051] ● A reservoir for containing the bioabsorbable sealed powder of the present invention;
[0052] ● An elongated hollow tubular structure having a proximal end and a distal end, the distal end having a powder outlet, and the proximal end being connected to the reservoir;
[0053] ● A manual air pump, preferably a ball or bellows, is arranged to generate an airflow that transports powder from the reservoir through the elongated hollow tubular structure to the powder outlet.
[0054] Another aspect of the present invention relates to a biocompatible flexible hemostatic sheet comprising:
[0055] ● A cohesive fiber carrier structure containing three-dimensional interconnected gap spaces; and
[0056] ●The bioabsorbable sealing powder of the present invention;
[0057] The sealing powder is distributed within the gap space and / or fixed to the fiber carrier structure.
[0058] This invention also relates to a kit for preparing a bioabsorbable sealed suspension, the kit comprising:
[0059] ● A first container or compartment containing a biocompatible liquid; and
[0060] ● A second container or compartment containing the bioabsorbable sealing powder of the present invention.
[0061] Another aspect of the present invention relates to a bioabsorbable sealed suspension comprising:
[0062] ●Biocompatible continuous liquid non-aqueous phase; and
[0063] ● A dispersion phase comprising the bioabsorbable sealing powder of the present invention. Detailed Implementation
[0064] Therefore, a first aspect of the present invention relates to a bioabsorbable sealing powder comprising:
[0065] (a) at least 5% by weight of a water-soluble electrophilic polymer carrying at least 3 reactive electrophilic groups, wherein the reactive electrophilic groups are capable of reacting with amine groups to form covalent bonds;
[0066] (b) 1% to 50% by weight of a water-soluble nucleophilic crosslinker carrying at least two reactive nucleophilic groups, which are capable of reacting with reactive electrophilic groups of an electrophilic polymer in the presence of water to form a covalent bond between the electrophilic polymer and the nucleophilic crosslinker;
[0067] (c) 1% to 60% by weight of absorbent particles, the absorbent particles containing at least 50% by weight of a water-insoluble polymer, the water-insoluble polymer containing a reactive nucleophilic group selected from amine groups, thiol groups and combinations thereof.
[0068] (d) 10% to 75% by weight of a water-soluble dispersant that is a solid at 20°C, wherein the water-soluble dispersant is selected from monosaccharides, disaccharides, oligosaccharides, sugar alcohols, and combinations thereof;
[0069] The combination of components (a), (b), (c) and (d) accounts for at least 60% by weight of the sealing powder;
[0070] The sealing powder has a tap density in the range of 0.3 g / ml to 0.9 g / ml;
[0071] At least 90% by weight of the powder has a diameter of less than 600 μm, and no more than 10% by weight of the powder has a diameter of less than 10 μm; and
[0072] Components (a), (b), (c) and (d) may be contained in the same particles or in different particles.
[0073] As used herein, the term "bioabsorbable sealant powder" refers to a sealant powder in which all components are reabsorbed by the body. Some components of the sealant powder, particularly the polymer components, gradually degrade within the body before being reabsorbed.
[0074] As used herein, the term "water-soluble electrophilic polymer" refers to an electrophilic polymer having a solubility of at least 50 g / L in demineralized water at 20 °C and pH 7. To determine the water solubility of nucleophilic polymers at different pH values, the pH of the demineralized water was adjusted using hydrochloric acid.
[0075] As used herein, the term "polyoxazoline" refers to poly(N-acylalkyleneimide) or poly(aromaticylalkyleneimide), and is also referred to as POx. An example of POx is poly(2-ethyl-2-oxazoline). The term "polyoxazoline" also includes POx copolymers.
[0076] As used herein, the term "water-soluble nucleophilic crosslinker" refers to a nucleophilic crosslinker having a solubility of at least 50 g / L in a demineralized solution at 20 °C and pH 7. To determine the water solubility of the nucleophilic crosslinker at different pH values, the pH of the demineralized solution was adjusted using hydrochloric acid.
[0077] Unless otherwise stated, as used herein, the term "protein" also includes cross-linked and hydrolyzed proteins. Similarly, unless otherwise stated, whenever a particular type of protein, such as gelatin or collagen, is mentioned, it includes both the hydrolyzed and cross-linked forms of that protein.
[0078] As used herein, the term "collagen" refers to the major structural protein in the extracellular spaces of various connective tissues in the animal body. Collagen forms a characteristic triple helix of three polypeptide chains. Depending on the degree of mineralization, collagenous tissue can be rigid (bone) or compliant (tendon), or have a gradient from rigid to compliant (cartilage). Unless otherwise stated, the term "collagen" also includes modified collagens other than gelatin (e.g., cross-linked collagen).
[0079] As used herein, the term "gelatin" refers to a mixture of peptides and proteins produced by the partial hydrolysis of collagen extracted from the skin, bones, and connective tissue of animals such as domestic cattle, chickens, pigs, and fish. During hydrolysis, the natural molecular bonds between individual collagen chains are broken down into forms that are more easily rearranged. As used herein, the term "gelatin" also includes modified gelatin, such as cross-linked gelatin and reduced cross-linked gelatin.
[0080] As used herein, the term "reduced crosslinked gelatin" refers to partially hydrolyzed crosslinked gelatin. Partial hydrolysis of peptide bonds in crosslinked gelatin can be achieved, for example, through alkali treatment. The hydrolysis of crosslinked gelatin results in an increase in the density of free carboxyl and free amine groups.
[0081] Unless otherwise stated, as used herein, the term "gelatin sponge" refers to a cross-linked gelatin material having a sponge-like structure.
[0082] The term "water-insoluble polymer containing reactive nucleophilic groups" refers to polymers containing reactive nucleophilic groups that have a solubility of less than 5 g / L in demineralized water at 20°C and pH 7. To determine the water solubility of water-soluble polymers at different pH values, the pH of the demineralized water was adjusted using hydrochloric acid.
[0083] Unless otherwise stated, as used herein, the term "hemostatic sheet" refers to a sheet capable of stopping bleeding from damaged tissue. The hemostatic sheet of the present invention achieves hemostasis by turning blood into a gel and / or by forming a seal to close the wound site.
[0084] As used herein, the term "water resistant" in relation to the fiber carrier structure means that the structure is not water soluble and does not disintegrate into a colloidal dispersion in water under neutral pH conditions (pH 7) and a temperature of 37°C.
[0085] As used herein, the term "gap space" refers to the void ("void") space within the fibrous carrier structure. The gap space within the fibrous carrier structure allows for the introduction of hemostatic powder into the structure. Blood and other bodily fluids can also enter the gap space, thereby allowing the hemostatic powder to exert its hemostatic effect and / or provide tissue adhesion to the hemostatic sheet.
[0086] As used herein, the term "tap density" refers to the density obtained by carefully filling a graduated cylinder (250 mL, 37 mm inner diameter) with 250 mL of powder, and then mechanically tapping the cylinder until no further volume reduction is observed. Tap density is calculated as mass divided by the final volume of the powder.
[0087] Unless otherwise stated, as used herein, the term "particle" includes both particles consisting of individual uniform particles and agglomerates of subparticles. Agglomerates can be prepared by granulation techniques known in the art, such as wet granulation.
[0088] Unless otherwise stated, as used herein, the term "liquid" means a liquid at a temperature of 20°C and a pressure of 1 atmosphere.
[0089] The diameter distribution of the sealing powder and the diameter distribution of its particulate components were appropriately determined by laser diffraction using a Malvern Mastersizer 2000 combined with a stainless steel sample dispersion unit. The sample dispersion unit was filled with approximately 120 ml of cyclohexane / ethyl ether (1:1 v / v) and stabilized at 1800 rpm for 5 to 10 minutes, followed by background measurements (Blanc measurements). The sample tube was shaken and rotated horizontally 20 times. Then, approximately 50 mg was dispersed in the cyclohexane-containing sample dispersion unit. After introducing the sample into the dispersion unit, the sample was stirred at 1800 rpm for 1.5 minutes before measurement to ensure proper dispersion of all particles. The dispersed particles were not subjected to ultrasonic treatment. The average particle size is expressed as D[4,3], i.e., the volume-weighted average diameter (ΣniDi). 4 ) / (ΣniDi 3 ).
[0090] In addition to components (a), (b), (c), and (d), the sealing powder of the present invention may suitably contain one or more other components, such as surfactants, buffers, and / or polysaccharides. Preferably, the combination of components (a), (b), (c), and (d) constitutes at least 80% by weight of the sealing powder, and most preferably at least 90% by weight.
[0091] The sealing powder preferably has a tap density in the range of 0.25 g / ml to 0.8 g / ml, more preferably 0.3 g / ml to 0.6 g / ml.
[0092] According to another preferred embodiment, at least 90% by weight of the sealing powder has a diameter of less than 500 μm, and no more than 10% by weight of the sealing powder has a diameter of less than 20 μm. More preferably, at least 90% by weight of the sealing powder has a diameter of less than 400 μm, and no more than 10% by weight of the sealing powder has a diameter of less than 40 μm.
[0093] Preferably, at least 50% by weight of the sealing powder has a diameter in the range of 65 μm to 300 μm, more preferably in the range of 80 μm to 280 μm, and most preferably in the range of 100 μm to 200 μm.
[0094] The sealing powder preferably has a volume-weighted average diameter (D[4,3]) in the range of 65 μm to 300 μm, more preferably 80 μm to 250 μm, and most preferably 125 μm to 180 μm.
[0095] The water-soluble electrophilic polymer contained in the sealing powder of the present invention is preferably selected from electrophilic polyoxazoline, electrophilic polyethylene glycol, and combinations thereof.
[0096] Preferably, the sealing powder contains 10% to 50% by weight, more preferably 20% to 30% by weight, of a water-soluble electrophilic polymer.
[0097] The solubility of the water-soluble electrophilic polymer in demineralized water at 20°C and pH 3-7 is preferably at least 100 g / L, more preferably at least 200 g / L.
[0098] The solubility of the water-soluble electrophilic polymer in acetone at 20°C is preferably less than 10 mg / L, more preferably less than 5 mg / L, and most preferably less than 1 mg / L.
[0099] The water-soluble electrophilic polymer preferably has a molecular weight of at least 2 kDa. More preferably, the molecular weight of the electrophilic polymer is from 5 kDa to 200 kDa, and most preferably from 10 kDa to 100 kDa.
[0100] The water-soluble electrophilic polymer and the water-soluble nucleophilic crosslinking agent are preferably combined in the sealing powder of the present invention, wherein the crosslinking reaction between the electrophilic polymers is minimized and the degradation of the electrophilic polymers is minimized. Therefore, in a very preferred embodiment of the present invention, the water-soluble electrophilic polymer in the sealing powder has a polydispersity index (PDI) of less than 2.0, more preferably less than 1.8, and most preferably less than 1.5.
[0101] The water-soluble electrophilic polymer preferably contains at least 4 reactive electrophilic groups, more preferably at least 8 reactive electrophilic groups, even more preferably at least 16 reactive electrophilic groups, and most preferably at least 32 reactive electrophilic groups.
[0102] Water-soluble electrophilic polymers typically carry an average of at least 10, more preferably at least 20, reactive electrophilic groups.
[0103] According to a particularly preferred embodiment, the electrophilic polymer is an electrophilic polyoxazoline.
[0104] Electrophilic polyoxazolines are preferably derived from polyoxazolines whose repeating units are represented by the following formula (I):
[0105] (CHR 1 ) m NCOR 2
[0106] Where R 2 and R 1 Each is independently selected from H and optionally substituted C.1-22 Alkyl, optionally substituted cycloalkyl, optionally substituted aralkyl, optionally substituted aryl; and m is 2 or 3.
[0107] Preferably, R in formula (I) 1 and R 2 Selected from H and C 1-8 Alkyl groups, or even more preferably selected from H and C, are also preferred. 1-4 Alkyl group. R 1 The most preferred value is H. The integer m in equation (I) is preferably equal to 2.
[0108] According to a preferred embodiment, the polyoxazoline is a polymer, more preferably a homopolymer of 2-alkyl-2-oxazoline, said 2-alkyl-2-oxazoline being selected from 2-methyl-2-oxazoline, 2-ethyl-2-oxazoline, 2-propyl-2-oxazoline, 2-butyl-2-oxazoline, and combinations thereof. Preferably, the polyoxazoline is a homopolymer of 2-propyl-2-oxazoline or 2-ethyl-oxazoline. Most preferably, the polyoxazoline is a homopolymer of 2-ethyl-oxazoline.
[0109] According to a particularly preferred embodiment, the electrophilic polyoxazoline comprises at least 20 oxazoline units, more preferably at least 30 oxazoline units, and most preferably at least 80 oxazoline units.
[0110] The electrophilic polyoxazoline preferably contains an average of at least 0.05 reactive electrophilic groups per oxazoline residue. Even more preferably, the electrophilic polyoxazoline contains an average of at least 0.1 reactive electrophilic groups per oxazoline residue. Most preferably, the electrophilic polyoxazoline contains an average of 0.12 to 0.5 reactive electrophilic groups per oxazoline residue.
[0111] Polyoxazolines may carry active electrophilic groups at their side chains (active electrophilic side groups), at their ends, or at both positions. The electrophilic polyoxazolines used according to the invention advantageously contain one or more reactive electrophilic side groups.
[0112] Typically, each monomer of the electrophilic polyoxazoline contains 0.03 to 0.5 reactive electrophilic side groups, more preferably 0.04 to 0.35 reactive electrophilic side groups, and even more preferably 0.05 to 0.25 reactive electrophilic side groups.
[0113] According to a preferred embodiment, the reactive electrophilic group of the electrophilic polyoxazoline is selected from carboxylic acid esters, sulfonates, phosphonates, pentafluorophenyl esters, p-nitrophenyl esters, p-nitrophenyl thioesters, acyl halide groups, acid anhydrides, ketones, aldehydes, isocyanates, thioisocyanates, isocyanates, epoxides, activated hydroxyl groups, alkenes, glycidyl ethers, carboxyl groups, succinimide esters, sulfosuccinimide esters, maleimide (maleimide group), ethylene sulfonyl, imide esters, acetoacetate esters, haloacetals, o-pyridyl disulfide, dihydroxybenzene derivatives, vinyl groups, acrylates, acrylamide, iodoacetamide, and combinations thereof. More preferably, the reactive electrophilic group is selected from carboxylic acid esters, sulfonates, phosphonates, pentafluorophenyl esters, p-nitrophenyl esters, p-nitrothiophenyl esters, acyl halide groups, acid anhydrides, ketones, aldehydes, isocyanates, thioisocyanates, isocyanates, epoxides, activated hydroxyl groups, glycidyl ethers, carboxyl groups, succinimidates, sulfosuccinimidates, imine esters, dihydroxyphenyl derivatives, and combinations thereof. Even more preferably, the reactive electrophilic group is selected from haloacetals, o-pyridyl disulfides, maleimides, vinyl sulfones, dihydroxyphenyl derivatives, vinyl groups, acrylates, acrylamides, iodoacetamides, succinimidates, and combinations thereof. Most preferably, the reactive electrophilic group is selected from maleimides, vinyl groups, acrylates, acrylamides, succinimidates, sulfosuccinimidates, and combinations thereof.
[0114] Examples of succinimide esters that may be used include succinimide glutarate, succinimide propionate, succinimide succinamide, succinimide carbonate, disuccinimide octanoate, bis(sulfosuccinimide) octanoate, dithiobis(succinimide propionate), bis(2-succinimideoxycarbonyloxy)ethyl sulfone, 3,3'-dithiobis(sulfosuccinimide-propionate), succinimide carbamate, sulfonyl... Succinimide (4-iodoacetyl)aminobenzoate, bis(sulfosuccinimide) octanoate, sulfosuccinimide-4-(N-maleimidemethyl)-cyclohexane-yl-carboxylic acid ester, dithiobis-sulfosuccinimide propionate, disulfosuccinimide tartrate; bis[2-(sulfosuccinimideoxycarbonyloxyethyl sulfone)], ethylene glycol bis(sulfosuccinimide succinate), dithiobis(succinimide propionate).
[0115] Examples of dihydroxyphenyl derivatives that may be used include dihydroxyphenylalanine, 3,4-dihydroxyphenylalanine (DOPA), dopamine, 3,4-dihydroxyhydrocinnamic acid (DOHA), norepinephrine, epinephrine, and catechol.
[0116] The water-soluble nucleophilic crosslinking agent used in the sealing powder of the present invention is preferably selected from nucleophilic polyoxazoline, nucleophilic polyethylene glycol, polyethyleneimine, proteins, and combinations thereof. More preferably, the nucleophilic crosslinking agent is selected from nucleophilic polyoxazoline, nucleophilic polyethylene glycol, and combinations thereof. Most preferably, the nucleophilic crosslinking agent is nucleophilic polyoxazoline.
[0117] The water-soluble nucleophilic crosslinking agent preferably contains at least 3 reactive nucleophilic groups, more preferably at least 4 reactive nucleophilic groups, even more preferably at least 8 reactive nucleophilic groups, and most preferably at least 10 reactive nucleophilic groups. Most preferably, these reactive nucleophilic groups are amine groups, and most preferably primary amine groups.
[0118] According to an embodiment of the present invention, the water-soluble nucleophilic crosslinking agent is nucleophilic polyethylene glycol (PEG). Preferably, the nucleophilic PEG contains at least 3, more preferably at least 5, and most preferably 8 reactive nucleophilic groups.
[0119] According to a particularly preferred embodiment, the nucleophilic crosslinking agent is a nucleophilic polyoxazoline. Preferably, the nucleophilic polyoxazoline contains at least 3, more preferably at least 5, and most preferably 8 to 20 reactive nucleophilic groups.
[0120] Preferably, each oxazoline residue of the nucleophilic polyoxazoline contains an average of at least 0.1 reactive nucleophilic groups. Most preferably, each oxazoline residue of the nucleophilic polyoxazoline contains an average of 0.12 to 0.5 reactive nucleophilic groups.
[0121] Preferably, the sealing powder contains 1.5% to 35% by weight, more preferably 2% to 20% by weight, and most preferably 3% to 10% by weight of a water-soluble nucleophilic crosslinking agent.
[0122] The solubility of the water-soluble nucleophilic crosslinking agent in demineralized water at 20°C and pH 7 is preferably at least 100 g / L, more preferably at least 200 g / L.
[0123] The solubility of the water-soluble nucleophilic crosslinking agent in acetone at 20°C is preferably less than 10 mg / L, more preferably less than 5 mg / L, and most preferably less than 1 mg / L.
[0124] According to a particularly preferred embodiment, the water-soluble nucleophilic crosslinking agent dissolves relatively slowly in water. It is believed that when the water-soluble electrophilic polymer reacts with the water-soluble nucleophilic crosslinking agent at a relatively slow rate, the electrophilic polymer can also react with proteins in the blood and tissue at the bleeding site. By using the relatively slowly dissolving water-soluble nucleophilic crosslinking agent, the dissolved electrophilic polymer has the opportunity to react with proteins in the blood and tissue, as well as with the (slow) water-soluble nucleophilic crosslinking agent, thereby producing a strong, homogeneous sealing gel.
[0125] Water-soluble nucleophilic crosslinking agents with high molecular weights tend to dissolve relatively slowly in water. Therefore, in a highly preferred embodiment, the water-soluble nucleophilic crosslinking agent has a molecular weight of at least 3 kDa, more preferably at least 10 kDa, and most preferably from 20 kDa to 3000 kDa.
[0126] If the water-soluble electrophilic polymer releases acidic substances upon reaction with nucleophilic groups, the present invention can appropriately utilize water-soluble nucleophilic crosslinking agents that are soluble at acidic pH. This is, for example, the case when the electrophilic polymer contains N-hydroxysuccinimide groups.
[0127] According to a preferred embodiment, the water-soluble nucleophilic crosslinking agent contains two or more amine groups, and the reactive electrophilic groups of the water-soluble electrophilic polymer are selected from carboxylic acid esters, sulfonates, phosphonates, pentafluorophenyl esters, p-nitrophenyl esters, p-nitrothiophenyl esters, acyl halide groups, acid anhydrides, ketones, aldehydes, isocyanates, thioisocyanates, isocyanates, epoxides, activated hydroxyl groups, glycidyl ethers, carboxyl groups, succinimidates, sulfosuccinimidates, imine esters, dihydroxyphenyl derivatives, and combinations thereof.
[0128] According to another preferred embodiment, the water-soluble nucleophilic crosslinking agent contains two or more thiol groups, and the reactive electrophilic group of the water-soluble electrophilic polymer is selected from haloacetals, o-pyridyl disulfides, maleimides, vinyl sulfones, dihydroxyphenyl derivatives, vinyl groups, acrylates, acrylamides, iodoacetamides, succinimidides, sulfosuccinimidides, and combinations thereof. More preferably, the reactive electrophilic group is selected from succinimidides, sulfosuccinimidides, haloacetals, maleimides, or dihydroxyphenyl derivatives and combinations thereof. Most preferably, the reactive electrophilic group is selected from maleimides or dihydroxyphenyl derivatives and combinations thereof.
[0129] The combination of water-soluble electrophilic polymer and water-soluble nucleophilic crosslinker preferably accounts for at least 20% by weight of the sealing powder, more preferably 20% to 60% by weight, and most preferably 25% to 35% by weight.
[0130] The ratio between the total number of reactive electrophilic groups provided by the water-soluble electrophilic polymer and the total number of reactive nucleophilic groups provided by the water-soluble nucleophilic crosslinker is preferably in the range of 1:0.05 to 1:0.4, more preferably in the range of 1:0.1 to 1:0.3, and most preferably in the range of 1:0.15 to 1:0.25.
[0131] The bioabsorbable sealing powder of the present invention preferably contains 10% to 60% by weight, more preferably 12% to 40% by weight, and most preferably 15% to 30% by weight of water-insoluble polymer containing reactive nucleophilic groups.
[0132] According to a particularly preferred embodiment, the absorbent particles are water-resistant, meaning that these particles are not water-soluble and do not disintegrate in water to form a colloidal dispersion under neutral pH conditions (pH 7) and a temperature of 37°C. Gelatin sponge particles can be suitably used as absorbent particles according to the invention.
[0133] The absorbent particles preferably contain at least 50%, more preferably at least 70%, of a water-insoluble polymer by weight of the absorbent particles, the water-insoluble polymer containing a reactive nucleophilic group selected from amine groups, thiol groups, and combinations thereof.
[0134] According to a particularly preferred embodiment, the absorbent particles contain at least 10% by weight, more preferably at least 15% by weight, of a water-insoluble polymer containing reactive amine groups.
[0135] The water-insoluble polymer containing reactive nucleophilic groups preferably has a water solubility of less than 3 g / L, more preferably less than 2 g / L, in demineralized water at 20°C and pH 7.
[0136] The solubility of the water-insoluble polymer containing reactive nucleophilic groups in acetone at 20°C is preferably less than 10 mg / L, more preferably less than 5 mg / L, and most preferably less than 1 mg / L.
[0137] The water-insoluble polymer containing reactive nucleophilic groups contained in the water-absorbing particles is preferably selected from proteins, deacetylated chitosans, and combinations thereof. Most preferably, the water-insoluble polymer containing reactive nucleophilic groups is a protein.
[0138] Deacetylated chitosan is a naturally occurring substance, a biodegradable, non-toxic complexed carbohydrate of chitin (poly-N-acetyl-D-glucosamine). Deacetylated chitosan is the deacetylated form of chitin. The deacetylated chitosan applied according to the present invention preferably has a degree of deacetylation greater than 50%. The deacetylated chitosan used according to the present invention preferably has a molecular weight of at least 5 kDa, more preferably from 10 kDa to 10,000 kDa.
[0139] Examples of proteins that can be used include gelatin, cross-linked gelatin, collagen, and combinations thereof. More preferably, cross-linked gelatin is a water-insoluble polymer containing reactive nucleophilic groups.
[0140] Crosslinked gelatin preferably has a molecular weight in the range of 30 kDa to 3,000 kDa, more preferably in the range of 400 kDa to 2,000 kDa, and most preferably in the range of 500 kDa to 1,500 kDa.
[0141] The preferred average primary amine content of cross-linked gelatin is 5 × 10⁻⁶ μg of reduced cross-linked gelatin. -4 μmol to 2×10 -2 μmol, more preferably 1.0 × 10 μmol. -3 μmol to 1.0 × 10 -2 Within the range of μmol primary amine.
[0142] The absorbent particles used in the sealing powder of the present invention preferably have a volume-weighted average diameter (D[4,3]) of at least 10 μm, more preferably in the range of 20 μm to 250 μm, and most preferably in the range of 25 μm to 180 μm.
[0143] The absorbent particles have an absorbency of at least 0.2 grams of water per gram of absorbent particles, more preferably 0.5 to 3 grams of water per gram of absorbent particles, and most preferably 0.8 to 2 grams of water per gram of absorbent particles. The absorbency can be appropriately determined by gravimetric analysis.
[0144] The water-soluble dispersant contained in the sealing powder of the present invention is preferably selected from sucrose, trehalose, lactose, maltitol, mannitol, sorbitol, xylitol, cyclodextrin, maltodextrin, dextran, and combinations thereof, and more preferably from sucrose, trehalose, mannitol, and combinations thereof.
[0145] The water-soluble dispersant preferably has a glass transition temperature higher than 30°C, more preferably a glass transition temperature of 50°C to 200°C, and most preferably a glass transition temperature of 75°C to 95°C.
[0146] Preferably, the sealing powder contains 25% to 70% by weight, more preferably 30% to 65% by weight, and most preferably 40% to 60% by weight of a water-soluble dispersant.
[0147] In a preferred embodiment, the sealing powder contains at least 30% by weight, more preferably at least 35% by weight, and most preferably at least 40% by weight of particles containing both components (a) and (d).
[0148] According to another preferred embodiment, the sealing powder contains at least 20% by weight, more preferably at least 30% by weight, and most preferably at least 40% by weight of particles containing both components (b) and (d).
[0149] According to a particularly preferred embodiment, the sealing powder contains at least 20% by weight, more preferably at least 30% by weight, and most preferably at least 40% by weight of particles comprising both components (b), (c), and (d).
[0150] The sealing powder of the present invention can be composed of particles having the same composition, or it can be a mixture of different particles. Examples of mixtures of different particles include:
[0151] (a)(i) a mixture of particles containing only components (a) and (d) and (ii) particles containing only components (b), (c) and (d).
[0152] (b)i) Particles containing only components (a) and (d), (ii) Particles containing only components (b) and (d), and (iii) Mixtures containing only components (c) and (d).
[0153] Here, the term "only" is used to indicate that, apart from the components described, the particles do not contain any other components of the sealing powder (a) to (d).
[0154] When the sealing powder is composed of a mixture of different particles, the powder preferably contains 30% to 70% by weight of particles containing only components (a) and (d) and 30% to 70% by weight of particles containing only components (b), (c), and (d). More preferably, the sealing powder contains 40% to 60% by weight of particles containing only components (a) and (d) and 40% to 60% by weight of particles containing only components (b), (c), and (d).
[0155] Preferably, particles containing only components (a) and (d) and particles containing only components (b), (c) and (d) together constitute at least 60% by weight, more preferably at least 80% by weight, and most preferably at least 90% by weight of the sealing powder.
[0156] In a particularly preferred embodiment, the sealing powder of the present invention contains at least 60% by weight, more preferably at least 80% by weight, and most preferably at least 90% by weight particles containing each of components (a), (b), (c), and (d). Such particles can be prepared, for example, by granulation of a mixture of the different particles described above.
[0157] According to another particularly preferred embodiment, the sealing powder contains at least 50% by weight, more preferably at least 70% by weight, and most preferably at least 80% by weight, particles containing each of components (a), (b), (c), and (d) in the form of agglomerates containing only subparticles A of components (a) and (d) and only subparticles B of components (b), (c), and (d). More preferably, the agglomerates of subparticles A and B contain 20% to 80% by weight of subparticle A and 20% to 80% by weight of subparticle B. More preferably, the agglomerates of subparticles A and B contain 40% to 60% by weight of subparticle A and 40% to 60% by weight of subparticle B.
[0158] Preferably, the particles of the sealing powder contain 0.05% to 5% by weight, more preferably 0.1% to 2% by weight, of a surfactant with a melting point of 30°C or higher.
[0159] In a preferred embodiment, the surfactant is selected from block copolymer surfactants, polyoxyethylene stearate, sodium dodecyl sulfate, and combinations thereof, more preferably poloxamer, and most preferably poloxamer 188 or poloxamer 407.
[0160] According to another preferred embodiment, the surfactant is contained in particles that also contain components (b) and (d), more preferably in particles that also contain components (b), (c) and (d), and most preferably in particles that also contain components (a), (b), (c) and (d).
[0161] Another aspect of the invention relates to a method for treating a wound or reducing bleeding at a bleeding site, the method comprising applying a sealing powder according to the invention topically to the wound or bleeding site.
[0162] Preferably, in the treatment method of the present invention, the powder is at a concentration of 5 mg / cm³. 2 Up to 250 mg / cm 2 The amount is more preferably 20 mg / cm³. 2 Up to 200 mg / cm 2 The optimal dosage is 50 mg / cm³. 2 Up to 125 mg / cm 2 Apply locally in appropriate amounts.
[0163] The method of the present invention is particularly applicable to a) wounds selected from minor abrasions, incisions, scratches, scrapes, burns, sunburns, ulcers, internal venous bleeding, and external venous bleeding; and b) surgical interventions selected from gastrointestinal surgery, surgery on solid organs; otolaryngological (ENT) surgical interventions, cardiovascular surgery, cosmetic surgery, spinal surgery, neurosurgery; lymphatic, bile duct, and cerebrospinal fluid (CSF) fistulas, thoracic and pulmonary surgery, thoracic surgery, air leaks during orthopedic surgery; gynecological surgery; vascular surgery and emergency surgery, liver resection, and soft tissue injury or surgery.
[0164] Another aspect of the present invention relates to a method for preparing the bioabsorbable sealing powder of the present invention, the method comprising the following steps:
[0165] (a) Provide particles A comprising a water-soluble electrophilic polymer and a water-soluble dispersant;
[0166] (b) Provide particles B comprising a water-soluble nucleophilic crosslinking agent, water-absorbing particles and a water-soluble dispersant;
[0167] (c) Combine particle A and particle B.
[0168] In the preparation method of the present invention, premature cross-linking reaction between the water-soluble electrophilic polymer on one hand and the water-soluble nucleophilic cross-linking agent and the water-insoluble polymer containing reactive nucleophilic groups on the other hand is effectively avoided.
[0169] Particle A preferably contains 20% to 90% by weight of a water-soluble electrophilic polymer and 10% to 80% by weight of a water-soluble dispersant. More preferably, particle A contains 30% to 70% by weight of a water-soluble electrophilic polymer and 30% to 70% by weight of a water-soluble dispersant. Most preferably, it contains 40% to 60% by weight of a water-soluble electrophilic polymer and 40% to 60% by weight of a water-soluble dispersant.
[0170] The water-soluble electrophilic polymer and the water-soluble dispersant together preferably constitute at least 60% by weight of particle A, more preferably at least 80% by weight, and most preferably at least 90% by weight.
[0171] Particle A is preferably prepared by agglomeration of water-soluble electrophilic polymer particles and water-soluble dispersant particles. Agglomeration is preferably achieved by wet granulation.
[0172] Particle B preferably contains 5% to 20% by weight of a water-soluble nucleophilic crosslinking agent, 25% to 60% by weight of water-absorbing particles, and 30% to 70% by weight of a water-soluble dispersant. More preferably, particle B contains 6% to 18% by weight of a water-soluble nucleophilic crosslinking agent, 30% to 50% by weight of water-absorbing particles, and 35% to 65% by weight of a water-soluble dispersant. Most preferably, particle B contains 8% to 15% by weight of a water-soluble nucleophilic crosslinking agent, 35% to 45% by weight of water-absorbing particles, and 40% to 60% by weight of a water-soluble dispersant.
[0173] The water-soluble nucleophilic crosslinking agent, the water-absorbing particles, and the water-soluble dispersant together preferably constitute at least 60% by weight of particle B, more preferably at least 80% by weight, and most preferably at least 90% by weight.
[0174] Particle B is preferably prepared by agglomeration of particles of a water-soluble nucleophilic polymer, particles of a water-insoluble absorbent polymer, and particles of a water-soluble dispersant. Agglomeration is preferably achieved by wet granulation.
[0175] The combination of particles A and B is preferably achieved by simple mixing or by granulation (to form agglomerates).
[0176] When particles A and B are combined by simple mixing, particle A preferably has a volume-weighted average diameter (D[4,3]) in the range of 25 μm to 300 μm, more preferably in the range of 80 μm to 250 μm, and most preferably in the range of 125 μm to 180 μm. In the case of simple mixing, the volume-weighted average diameter (D[4,3]) of particle B preferably is in the range of 25 μm to 300 μm, more preferably in the range of 80 μm to 250 μm, and most preferably in the range of 125 μm to 180 μm.
[0177] Preferably, particles A and B are combined into an agglomerate. According to a particularly preferred embodiment, particles A and B are combined into an agglomerate by wet granulation. More preferably, particles A and B are combined into an agglomerate using a non-aqueous granulation liquid containing at least 60% by weight of an organic solvent selected from acetone, isopropanol, ethanol, methanol, diethyl ether, heptane, hexane, pentane, cyclohexane, dichloromethane, and mixtures thereof. More preferably, the non-aqueous granulation liquid contains at least 60% by weight, most preferably at least 85% by weight of an organic solvent selected from acetone, isopropanol, ethanol, and mixtures thereof. Even more preferably, the non-aqueous granulation liquid contains at least 60% by weight, most preferably at least 85% by weight of acetone.
[0178] When particles A and B are combined by granulation, particle A preferably has a volume-weighted average diameter (D[4,3]) in the range of 10 μm to 200 μm, more preferably in the range of 20 μm to 150 μm, and most preferably in the range of 25 μm to 120 μm. In the case of granulation, the volume-weighted average diameter (D[4,3]) of particle B preferably is in the range of 10 μm to 200 μm, more preferably in the range of 20 μm to 150 μm, and most preferably in the range of 25 μm to 120 μm.
[0179] The non-aqueous granulation liquid preferably contains no more than 1% by weight of water, more preferably no more than 0.1% by weight of water.
[0180] In the method of the present invention for combining particles A and B, the amount of non-aqueous granulation liquid used is preferably 0.5% to 5% by weight of the combined amount of particles A and B. More preferably, the amount of non-aqueous granulation liquid used is 1% to 4% by weight of the combined amount of particles A and B, and most preferably 1.5% to 3% by weight.
[0181] Another aspect of the present invention relates to an apparatus for powder application, the apparatus comprising:
[0182] ● A reservoir for containing the bioabsorbable sealed powder according to the invention;
[0183] ● An elongated hollow tubular structure having a proximal end and a distal end, the distal end having a powder outlet, and the proximal end being connected to the reservoir;
[0184] ● A manual air pump is attached to the reservoir and arranged to generate an airflow that transports powder from the reservoir through the elongated hollow tubular structure to the powder outlet.
[0185] According to a preferred embodiment, the device includes a porous filter disposed within a reservoir, between an air pump and a powder outlet; wherein powder is disposed within the reservoir, between the filter and the powder outlet, and wherein the pump is in fluid communication with the powder outlet through the porous filter and through the powder. The filter is preferably impermeable to the powder contained in the reservoir.
[0186] Preferably, the manual air pump includes a bellows.
[0187] The sealing powder of the present invention can be advantageously applied to hemostatic sheets to improve their adhesion and hemostatic properties. Therefore, another aspect of the invention relates to a biocompatible flexible hemostatic sheet comprising:
[0188] ● A cohesive fiber carrier structure containing three-dimensional interconnected gap spaces; and
[0189] ●The bioabsorbable sealing powder according to the present invention;
[0190] The sealing powder is distributed within the gap space and / or fixed to the fiber carrier structure.
[0191] The sealing powder can be suitably fixed to the fibrous carrier structure by an adhesive, which includes a binder, preferably a fusible solid binder. Examples of such binders include powders based on polyester, polypropylene, acrylic, or polyethylene.
[0192] According to a preferred embodiment, the sealing powder is distributed within the interstitial spaces of the fiber carrier.
[0193] The cohesive fiber carrier structure of the hemostatic sheet is preferably water-resistant.
[0194] According to a particularly preferred embodiment, the hemostatic sheet of the present invention is bioabsorbable. Reabsorption of the carrier structure and sealing powder typically requires the chemical breakdown (e.g., hydrolysis) of the polymer contained therein. Complete absorption of the hemostatic sheet by the human body typically occurs within 1 to 10 weeks, preferably within 2 to 8 weeks.
[0195] The hemostatic sheet of the present invention typically has an uncompressed average thickness of 0.5 mm to 25 mm. More preferably, the uncompressed average thickness is in the range of 1 mm to 10 mm, and most preferably in the range of 1.5 mm to 5 mm.
[0196] The preferred size of the hemostatic sheet is such that the top and bottom of the sheet each have a diameter of at least 2 cm. 2 More preferably at least 10cm 2 And the optimal size is 25cm. 2 Up to 50cm 2 The surface area. Typically, the sheet is rectangular in shape and has a length of 25mm to 200mm and a width of 25mm to 200mm.
[0197] The preferred hemostatic tablets have a concentration of less than 200 mg / cm³. 3 More preferably less than 150 mg / cm 3 And the optimal value is 10 mg / cm³. 3 Up to 100 mg / cm 3 The uncompressible density.
[0198] The hemostatic sheet of the present invention is preferably substantially anhydrous. Typically, the hemostatic sheet has a water content of no more than 5% by weight, more preferably no more than 2% by weight, and most preferably no more than 1% by weight.
[0199] The water absorption capacity of the hemostatic sheet is preferably at least 50%, more preferably in the range of 100% to 800%, and most preferably in the range of 200% to 500%.
[0200] The hemostatic sheet of the present invention is preferably sterile.
[0201] The advantage of using a fibrous carrier structure in the hemostatic sheet of the present invention is that the sealing powder can be uniformly distributed throughout the carrier structure without difficulty. Such uniform distribution is difficult to achieve, for example, in a foamed carrier structure.
[0202] The fibers in the fiber carrier structure preferably have an average diameter of 1 μm to 500 μm, more preferably 2 μm to 300 μm, and most preferably 5 μm to 200 μm. The average diameter of the fibers can be appropriately determined using a microscope.
[0203] Typically, at least 50% by weight, more preferably at least 80% by weight, of the fibers in the fiber carrier structure have a diameter of 1 μm to 300 μm and a length of at least 1 mm.
[0204] Preferably, at least 50% by weight of the fiber carrier structure, more preferably at least 80% by weight of the fiber has an aspect ratio (length to diameter ratio) of at least 1000.
[0205] The fiber carrier structure used in this invention is preferably a felt structure, a woven structure, or a knitted structure. Most preferably, the fiber carrier structure is a felt structure. Here, the term "felt structure" refers to a structure produced by laying and pressing fibers together to form an adhesive material.
[0206] The fiber carrier structure preferably comprises at least 50% by weight, more preferably at least 80% by weight, and most preferably at least 90% by weight of fiber, which contains fiber polymers selected from the following: gelatin, collagen, cellulose, modified cellulose, carboxymethyl dextran, lacto-glycolic acid copolymer PLGA, sodium hyaluronate / carboxymethyl cellulose, polyvinyl alcohol, deacetylated chitosan, and combinations thereof.
[0207] According to a particularly preferred embodiment, the fiber carrier structure comprises at least 50% by weight, more preferably at least 80% by weight, and most preferably at least 90% by weight of fibers containing gelatin and / or modified cellulose. The gelatin preferably used is cross-linked gelatin. The modified cellulose preferably used is oxidized cellulose, and most preferably oxidized regenerated cellulose.
[0208] In another preferred embodiment, the fiber carrier structure comprises at least 50% by weight, more preferably at least 80% by weight, and most preferably at least 90% by weight of fiber, the fiber containing at least 80% by weight of one or more of the aforementioned fiber polymers.
[0209] The preferred fiber carrier structure has an open-pore structure with an air permeability of at least 0.1 L / min × cm. 2 More preferably at least 0.5 L / min × cm 2 Air permeability was determined according to EN ISO 9237:1995 (Textiles—Determination of air permeability of fabrics).
[0210] The fibers in the fiber carrier structure can be produced by methods known in the art, such as electrospinning, electroblowing, and high-speed rotary atomizer spinning. The production of fiber carrier structures by high-speed rotary atomizer spinning is described in US 2015 / 0010612. Commercially available hemostatic fiber sheets can also be used as the fiber carrier structure.
[0211] The sealing powder is preferably present in the hemostatic sheet of the present invention in an amount of 5% to 90%, more preferably 10% to 80%, even more preferably 20% to 75%, and most preferably 50% to 70%, based on the weight of the fiber carrier structure.
[0212] Another aspect of the present invention relates to a kit for preparing a bioabsorbable sealed suspension, the kit comprising:
[0213] ● A first container or compartment containing a biocompatible liquid; and
[0214] ● A second container or compartment containing the bioabsorbable sealing powder of the present invention.
[0215] The above-described kit can be used to prepare a bioabsorbable suspension by mixing a biocompatible liquid with a sealing powder. The resulting suspension can be advantageously applied, for example, to fill and seal pleural cavities or hemorrhages.
[0216] The biocompatible liquid preferably contains one or more biocompatible liquids selected from the following: polyethylene glycol, propylene glycol, triethyl citrate, polyglycerol, DMSO, glycerol, glyceryl diacetate, triacetin, N-methylpyrrolidone (NMP), water, and mixtures thereof. The polyethylene glycol used in the suspension preferably has a molecular weight of not more than 550 g / mol, more preferably not more than 450 g / mol.
[0217] The biocompatible liquid in the kit of the present invention may suitably contain water. The presence of water in the biocompatible liquid enables a cross-linking reaction to occur between the components of the sealing powder before the sealing suspension is applied to the tissue. These initial cross-linking reactions will make the suspension more viscous and sticky, which facilitates the application of the suspension to the tissue. The water content of the biocompatible liquid is preferably in the range of 1% to 50% by weight, more preferably not more than 2% to 30% by weight, and most preferably not more than 3% to 10% by weight.
[0218] Biocompatible liquids may appropriately contain buffers and / or viscosity modifiers, such as hyaluronic acid, alginate, carboxymethyl cellulose, and combinations thereof.
[0219] Another aspect of the present invention relates to a bioabsorbable sealed suspension comprising:
[0220] • Biocompatible continuous liquid non-aqueous phase; and
[0221] • A dispersion containing the bioabsorbable sealing powder according to the invention.
[0222] The non-aqueous phase of the sealed suspension preferably contains one or more biocompatible liquids selected from the following: polyethylene glycol, propylene glycol, triethyl citrate, polyglycerol, DMSO, glycerol, glyceryl diacetate, triacetin, N-methylpyrrolidone (NMP), and mixtures thereof. The polyethylene glycol used in the suspension preferably has a molecular weight of not more than 550 g / mol, more preferably not more than 450 g / mol.
[0223] The water content of the non-aqueous phase is preferably no more than 3% by weight, more preferably no more than 1% by weight, and most preferably no more than 0.3% by weight.
[0224] In addition to the sealing powder, the non-aqueous phase may suitably contain other components such as buffers and viscosity modifiers (e.g., hyaluronic acid, alginate, and / or carboxymethyl cellulose).
[0225] The sealing suspension preferably contains 5% to 75% by weight, more preferably 10% to 40% by weight, and most preferably 15% to 30% by weight of sealing powder.
[0226] As the particles of the sealing powder in the suspension may begin to sink or float over time, the suspension may need to be shaken or stirred before use.
[0227] The present invention is further illustrated by the following non-limiting examples.
[0228] Example
[0229] Generally speaking: unless otherwise specified, the content is less than 2.0% w / w.
[0230] Preparation of NHS-POx
[0231] The following synthesis was performed of a poly[2-(ethyl / hydroxy-ethyl-amide-ethyl / NHS-ester-ethyl-ester-ethyl-amide-ethyl)-2-oxazoline] terpolymer containing 20% NHS-ester groups (=EL-POx, 20% NHS) with activated NHS-side chains:
[0232] Poly[2-(ethyl / methoxy-carbonyl-ethyl)-2-oxazoline] copolymer (DP = + / -100) was synthesized via CROP using 60% 2-ethyl-2-oxazoline (EtOx) and 40% 2-methoxycarbonyl-ethyl-2-oxazoline (MestOx). A statistical copolymer containing 40% 2-methoxycarbonyl-ethyl groups was obtained. 1 H-NMR).
[0233] Second, the polymer containing 40% 2-methoxycarbonyl-ethyl groups is reacted with ethanolamine to produce a copolymer having 40% 2-hydroxy-ethyl-amide-ethyl groups. 1 (H-NMR). Subsequently, half of the 2-hydroxy-ethyl-amide-ethyl group reacts with succinic anhydride to give the product according to... 1 H-NMR is a terpolymer containing 60% 2-ethyl groups, 20% 2-hydroxy-ethyl-amide-ethyl groups and 20% 2-carboxy-ethyl-ester-ethyl-amide-ethyl groups.
[0234] Finally, EL-POx, 20% NHS, corresponding to 100% NHS functionalization (NHS-DF), was generated by activating the 2-carboxy-ethyl-ester-ethyl-amide-ethyl- group with N-hydroxysuccinimide (NHS) and diisopropylcarbodiimide (DIC). 1 H-NMR, NHS-POx contains 20% NHS-ester groups.
[0235] NHS-POx was dissolved in water (60 g in 300 mL) between 2°C and 8°C, cooled at -80°C for half an hour, and freeze-dried. The freeze-dried powder thus obtained was dried in a rotary evaporator at 40°C until the water content, as determined by Karl Fischer titration, was less than 0.8% w / w. The dried (white) powder was milled using a ball mill (Retch MM400) until the average particle size was no greater than 40 μm (D[4,3]) and vacuum-sealed in an aluminum-aluminum bag.
[0236] Dyeing of NHS-POx powder
[0237] 31.25 mg of Dyestuff Blue 1 (CAS 3844-45-9, Spectrum Chem., VWR) was dissolved in 500 mL of cold ultrapure water using an Ultra-Turrax (IKA) high-performance dispersant. After mixing (5 min), 62.5 g of NHS-POx was dissolved in FD&C solution using an Ultra-Turrax (IKA) high-performance dispersant. The solution was rapidly frozen immediately after mixing (5 min) and then freeze-dried. The freeze-dried powder was dried at 40 °C in a rotary evaporator until the residual water content was less than 0.8% w / w as determined by Karl Fischer titration. The dried (blue) powder was then milled using a ball mill (Retch MM400) until the blue-dyed NHS-POx powder had an average particle size of no more than 40 μm (D[4,3]) and vacuum-sealed in an aluminum-aluminum bag. 1 H-NMR spectroscopy analysis of co-lyophilized NHS-POx. 15 mg of the co-lyophilized powder was dissolved in deuterated dimethyl sulfoxide (DMSO-d6). The sample was transferred to an NMR tube and the readings were recorded. 1 1H-NMR spectra. From the obtained spectra, the amount of NHS bound to NHS-POx was calculated: the average NHS-DF was 90% to 100%.
[0238] Preparation of NU-POx
[0239] Polyoxazoline containing ethyl and amino groups in the alkyl side chain was synthesized by CROP of EtOx and MestOx and subsequent amidation of the methyl ester side chain with ethylenediamine to produce poly(2-ethyl / aminoethylamide ethyl-2-oxazoline) copolymer (NU-POx).
[0240] according to 1 ¹H-NMR showed that NU-POx contained 10% NH₂. NU-POx was dissolved in water (60 g in 300 mL) between 2°C and 8°C, cooled to -80°C for half an hour, and then freeze-dried. The freeze-dried powder was dried in a rotary evaporator at 40°C until the water content was less than 0.8% w / w as determined by Karl Fischer titration. The dried powder was then ground in a shredder (Retsch GM200) until the average particle size was no greater than 100 μm (D[4,3]) and vacuum-sealed in an aluminum-aluminum bag.
[0241] Preparation of NHS-POx / sugar mixtures by co-freeze-drying (Method A1)
[0242] The following is a co-freeze-dried NHS-POx / sugar powder preparation:
[0243] 15 g of sugar was dissolved in 200 mL of cold ultrapure water using an Ultra-Turrax (IKA) dispersant. Then, after mixing (3 minutes), 15 g of blue-stained NHS-POx was dissolved in the sugar mixture using the same dispersant. Immediately after mixing (3 minutes), the solution was frozen in liquid nitrogen and freeze-dried.
[0244] The freeze-dried powder was dried in a rotary evaporator at 40°C until the residual water content, as determined by Karl Fischer titration, was less than 0.8% w / w. The dried powder was then ground in a shredder until the particle size was no greater than 63 μm and vacuum-sealed in aluminum-aluminum bags.
[0245] use 1 1H-NMR spectroscopy analysis of co-lyophilized NHS-POx / sugar (1:1 w / w): 15 mg of the co-lyophilized powder was dissolved in deuterated dimethyl sulfoxide (DMSO-d6). The sample was transferred to an NMR tube and the readings were recorded. 1 H-NMR spectra. NHS-DF was calculated from the obtained spectra, with an average value between 85% and 100%.
[0246] Preparation of NHS-POx / sugar granules (Method A2)
[0247] The following steps are used to prepare NHS-POx / sugar granules:
[0248] Add 23g of co-lyophilized NHS-POx / sugar according to method A1 to a mortar. Then, during mixing, slowly add 10mL of acetone:water (95:5 v / v) in 1mL increments. Dry the granules under reduced pressure in a rotary evaporator at 40°C for 1 hour, and then grind them in a shredder for 10 seconds. Dry the ground granules again under reduced pressure until... 1 The acetone content was less than 0.2% and the water content was less than 0.8%, as determined by H-NMR and Karl Fischer titration.
[0249] The dried granules are ground again until the particle size is within the desired range (see below) and then vacuum-sealed in an aluminum-aluminum bag.
[0250] NHS-POx / sugar granules (1:1 w / w) were analyzed by 1H-NMR spectroscopy: 25 mg of granules were dissolved in deuterated dimethyl sulfoxide (DMSO-d6) containing maleic acid (3 mg / mL) as an internal standard (1.0 mL), transferred to an NMR tube, and the 1H-NMR spectra were recorded. The NHS-DF was calculated from the obtained spectra, with an average value between 85% and 100%.
[0251] Preparation of NU-POx / gelatin sponge / sugar granules (Method B1)
[0252] Weigh 0.2 g NU-POx, 0.8 g gelatin sponge (GELITA-SPON powder, purchased from Gelita Medical AG, Germany, unless otherwise specified) and 0.8 g sugar and place them in a mortar. Granulate the excipient with 50% w / w ultrapure water. Dry the wet granules in a 70°C oven until the water content is less than 0.5% as determined by Karl Fischer titration. Grind the dried granules until they have the desired particle size range (see below). The reactivity of the granules can be controlled by adjusting the pH to 9.5 with NaOH or to 9.2 using borate buffer before drying.
[0253] Preparation of NU-POx / gelatin sponge / sugar / surfactant particles (Method B2)
[0254] NU-POx / gelatin sponge / sugar granules are prepared as described in method B1, wherein a surfactant dissolved in ultrapure water used for granulation is added to obtain 0.10% w / w to 0.50% w / w surfactant in the final granules containing NHS-POx / sugar and NU-POx / gelatin sponge / sugar.
[0255] Preparation of NHS-POx sugar / NU-POx / gelatin sponge / sugar / surfactant powder mixture (Method C1)
[0256] The powder mixture is prepared as follows:
[0257] NHS-POx sugar powder (Method A2, particle size as needed) and NU-POx / gelatin sponge / sugar / surfactant particles (Method B1 or B2, particle size as needed) are added to a vial in a 1:1 weight ratio, mixed by shaking, and vacuum sealed in an aluminum-aluminum bag.
[0258] Preparation of NHS-POx sugar / NU-POx / gelatin sponge / sugar / surfactant powder mixture (method C2)
[0259] The powder mixture is prepared as follows:
[0260] NHS-POx sugar powder (Method A1, particle size <63μm) and NU-POx / gelatin sponge / sugar /
[0261] Surfactant particles (method B1 or B2, depending on the required particle size) are added to a mortar in a 1:1 weight ratio, dry-mixed, and vacuum-sealed in an aluminum-aluminum bag.
[0262] Preparation of NHS-POx sugar / NU-POx / gelatin sponge / sugar / surfactant particles (method C3) .
[0263] The granules were prepared as follows: NHS-POx sugar granules (Method A2, particle size <63 μm) and NU-POx / gelatin sponge / sugar / surfactant granules (Method B2, particle size <63 μm) were introduced into a mortar at a weight ratio of 1:1. Subsequently, acetone was added at a total of 1 mL / g per 1 mL portion during grinding and mixing.
[0264] The particles thus obtained are dried under reduced pressure until... 1 The acetone content determined by H-NMR was less than 0.2%. The dried particles were ground in a mortar until the particle size was between 125 μm and 180 μm, and then vacuum-sealed in an aluminum-aluminum bag.
[0265] NHS-POX / sugar granules (1:1) were analyzed by 1H-NMR spectroscopy. 25 mg of granules were dissolved in deuterated dimethyl sulfoxide (DMSO-d6) containing maleic acid (3 mg / mL) as an internal standard (1.0 mL), transferred to an NMR tube, and the 1H-NMR spectra were recorded. NHS-DF was calculated from the obtained spectra, with an average value between 85% and 100%.
[0266] Grinding and sieving
[0267] Grinding is performed using a mortar and pestle or a shredder (Retsch GM 200). Sieving is then performed to obtain fractions with the desired particle size and particle size distribution. For this purpose, a Retsch AS 200 sieving column with sieves of the following sizes is used: 45 μm, 63 μm, 90 μm, 125 μm, 180 μm, 250 μm, and 500 μm. To obtain the desired particle size, the powder is ground and sieved; by sampling the desired sieve fractions, the appropriate powder particle size range is obtained.
[0268] Apply powder to areas of perforation bleeding, abrasion bleeding, and lung injury.
[0269] Perforation bleeding (via vial): Contain a certain amount of powder in a sealed vial with a diameter of 15 mm. Apply the powder directly to the perforation bleeding area by pouring it from the vial. Once sufficient coverage of the bleeding is achieved, apply pressure with a 0.9% NaCl-moistened gauze for 1 minute, and then carefully remove the moistened gauze.
[0270] Abrasions (via bellows): A certain amount of powder is applied via a bellows application device with an 80mm long application tube. The powder is applied directly to the injury (abrasion) by blowing it off, and the hemostatic effect is assessed after 1 minute. If hemostasis is not achieved by covering the abrasion area completely, additional pressure is applied with 0.9% NaCl-moistened gauze for 1 minute, and the gauze is carefully removed.
[0271] Lung injury: Apply the powder manually to a 5cm x 5cm square area around the lung surface surrounding the standardized defect. Once uniform coverage is achieved, apply pressure with a 0.9% NaCl-moistened gauze for 2 minutes, adjusting the hand position after 1 minute to prevent irregularities in the final hydrogel, and carefully remove the moistened gauze.
[0272] Hemostasis and sealing test
[0273] Standardized in vitro and in vivo porcine hemorrhage models were used to assess hemostatic efficacy. All models were used with heparin to increase clotting time to approximately 2 to 3 times the activated clotting time (ACT).
[0274] In vitro model A live in vitro pig model with fresh livers was perfused with heparinized fresh blood from the slaughterhouse to simulate the real in vivo conditions as closely as possible. The livers were mounted on a perfusion machine, which maintained oxygenation, blood pH, temperature, and blood pressure within in vivo limits. Two livers and 10 liters of heparinized blood (5000 units / L) were collected at the slaughterhouse. The livers were transported on ice; the blood was prepared at ambient temperature. Within 2 hours of collection, liver damage was examined and sealed with gloves and cyanoacrylate glue.
[0275] ● Infusion parameters: Flow rate 600 ml / min; pressure 10 mmHg to 12 mmHg; temperature 37℃ (+ / -1℃); 0.25 liters of carbon-oxygen per minute;
[0276] ● Use a biopsy puncture instrument to create a circular bleeding wound (8mm in diameter) on the surface of the liver, cover it with rubber so that the depth of the bleeding is always 3mm, or alternatively use sandpaper to create an abrasion (3cm×3cm) (approximately 1mm deep).
[0277] ●After the liver is properly perfused (check color and temperature), test the sample according to the following procedure: turn on the camera; number the site on the camera; insert an 8mm biopsy puncture needle; remove the biopsy site; remove blood from the bleeding site with gauze (2x); collect blood in pre-weighed gauze for 30 seconds; score the bleeding.
[0278] ● Apply the hemostatic powder to the bleeding site (perforation or abrasion), and in the case of bleeding from a perforation, use a moist gauze (saline) to distribute the powder and press for one minute;
[0279] ● Observe and score the sealing and hemostasis.
[0280] in vivo model Standardized combined penetrating splenic rupture was performed on anesthetized pigs (domestic males, weight range: 40kg to 100kg adults). Midline laparotomy was performed to access the spleen and other organs. Using a scalpel, n=3 standardized subcapsular lesions (10mm × 10mm) were made. Hemostatic powder was applied under gentle pressure through pre-moistened gauze (saline) and held for 1 minute, followed by sealing and hemostasis scoring.
[0281] Sealing test
[0282] A standardized extracorporeal ventilation model of pig lungs was used to evaluate the sealing capability in the absence of blood, more specifically, the aerostatic efficiency.
[0283] In vitro model Freshly collected porcine heart and lung samples were ordered from the slaughterhouse and transported to the research facility on ice. After removing all excess tissue, ligating the main pulmonary artery, and suturing any remaining tissue in the left atrium, selective intubation and ventilation of the tail lobe were performed after lung re-expansion using manual inflation and manual lung recruitment techniques.
[0284] In the experimental setup, the lung was floated on 0.9% NaCl (37°C) and photographed from below for visual leak assessment. Measurements were performed at increased platform ventilation pressure (Pplat) during each measurement. The mechanical ventilator was set to pressure-controlled ventilation, respiratory rate 12 / min, inspiratory to expiratory ratio 1:2, positive end-expiratory pressure (PEEP) 5 cm H2O, and pressure 5 cm H2O above PEEP. Every 90 seconds, the pressure above PEEP was increased by 5 cm H2O until a platform of 40 cm H2O was reached.
[0285] ● First, baseline measurements are performed using this measurement scheme in order to conduct compliance measurements.
[0286] ●Then, with the lung inflated to 10 cm H2O PEEP, a standardized 25 mm × 25 mm surface pleural defect was created on the dorsal side of the caudate lobe by cutting the pleural edge at a 45° angle using the grinding wheel attachment on a Dremel and then carefully peeling away the central pleura with forceps and scissors. Baseline leak measurements were then performed using the same protocol.
[0287] ●The sealing powder is then manually applied to a 5×5cm square area around the standardized defect on the lung surface, and the lung is inflated at PEEP of 0cmH2O to 5cmH2O (if air leaks through the dry powder, reduce the PEEP until the problem is resolved). Once uniform coverage is achieved, pressure is applied for 2 minutes with a 0.9% NaCl-dampened gauze, adjusting the hand position after 1 minute to prevent irregularities in the final hydrogel. After carefully removing the gauze, the hydrogel is allowed to solidify again for 5 minutes in a measuring device (0.9% NaCl, 37°C).
[0288] ●Based on Macchiarini et al. (Macchiarini P, Wain J, Almy S, Dartevelle P. Experimental and clinical evaluation of a new synthetic, absorbable sealant to reduce air leaks in thoracic operations. J Thorac Cardiovasc Surg. 1999; 117(4):751-8), quantitative leakage (Pplat) was measured and failure modes were visually assessed.
[0289] A sealing rating system for powder at bleeding sites (based on an assessment of adhesion and cohesion 1 minute after application):
[0290] +++ Very strong seal (the seal only breaks when more than 80% by weight of powder is removed by scraping).
[0291] ++Strong seal (the seal breaks when some powder is removed by scraping).
[0292] + Good sealing (the seal will break when the powder is mechanically handled).
[0293] + / - Moderate seal (seal breaks when surrounding tissue is manipulated)
[0294] - No seal achieved
[0295] Hemostasis scoring system for powder applied to bleeding sites 1 minute after administration:
[0296] +++ Very strong hemostatic effect (the powder only fills with blood at the powder-damage interface; bleeding stops).
[0297] ++Strong hemostatic agent (The powder portion is filled with blood. A blood-free powder layer remains on top; bleeding stops)
[0298] + Excellent hemostasis (powder completely fills the blood; bleeding stops).
[0299] + / - Moderate hemostasis (powder completely fills the blood, some blood passes through)
[0300] - Bleeding was not stopped (the bleeding did not stop).
[0301] Before removal, the wetting score of the powder at the bleeding site was measured 1 minute after applying gauze soaked in saline (0.9% NaCl) (wetting was scored 4 minutes after gauze removal by measuring the depth of the powder penetration layer):
[0302] - Saltwater is difficult for the powder layer to absorb; only the surface of the powder layer is wet, and droplets of saltwater easily roll off the powder surface.
[0303] + / - Saltwater has partially penetrated the powder layer.
[0304] +The salt water has completely penetrated the powder layer
[0305] Comparative Example A
[0306] EL-POx was dry-mixed by co-grinding (with a mortar and pestle) with gelatin sponge alone (EL-POx:gelatin sponge = 1:0.8 w / w) or with gelatin sponge and NU-POx (EL-POx:gelatin sponge:Nu-POx = 1:0.8:0.2 w / w). The tap density of both powders was less than 0.2 g / mL.
[0307] The sealing and hemostatic properties (heparinized) of these two powders and two commercially available hemostatic powders were tested in an in vitro porcine liver system. The powders were applied in 1-gram doses.
[0308] The test results are summarized in Table 1.
[0309] Table 1
[0310]
[0311] 1 Powder, Gelita Medical AG, Germany
[0312] 2 Arista AH, Bard, USA
[0313] Example 2
[0314] A powder mixture (powder mixture 1) was prepared by method C2 using the powder obtained by method A1 (EL-POX:sugar = 1:1 w / w) and the powder obtained by method B1. In both powders, trehalose was used as the sugar component. A powder mixture (powder mixture 2) of the same composition was prepared by method C1 using the powder obtained by method A2 (EL-POX:sugar = 1:1 w / w, granulation using acetone / water (95:5) as the granulation liquid) and the powder obtained by method B1.
[0315] The sealing and hemostatic properties of the two powders (heparinized) were tested in an in vitro porcine liver system. The powders were applied in doses of 0.5 g.
[0316] The test results are summarized in Table 2.
[0317] Table 2
[0318] Powder mixture 1 <63 + / - + / - + Powder mixture 2 63-125 + + +
[0319] Example 3
[0320] Three different powder mixtures were prepared by method C1 using powder obtained by method A2 (EL-POX:sugar = 1:1 w / w) and three different powders obtained by method B1. In all powders, trehalose was used as the sugar component.
[0321] The only difference between the three powder mixtures is that the powder obtained by method B1 contains different amounts of NU-POx:
[0322] Powder mixture 1 2:8:8 Powder mixture 2 1:8:8 Powder Mixture 3 3:8:8
[0323] The sealing and hemostatic properties of the two powders (heparinized) were tested in an in vitro porcine liver system. The powders were applied in doses of 0.5 g.
[0324] The test results are summarized in Table 3.
[0325] Table 3
[0326] Powder mixture 1 63-125 + + + Powder mixture 2 63-125 - + / - + Powder Mixture 3 63-125 + + +
[0327] Example 4
[0328] Two different powders were prepared by mixing 1 part by weight of NHS-POx powder (sugar-free) with 2 parts by weight of powder containing trehalose obtained by method B1 or 1 part by weight of powder without any sugar obtained by method B1.
[0329] The composition of the powder obtained by method B1 is as follows:
[0330] Powder mixture 1 2:8:8 Powder mixture 2 2:8:0
[0331] The sealing and hemostatic properties of these two powders (heparinized) were tested in an in vitro porcine liver system. A bellows application device was used. Apply the powder in 0.5g amounts.
[0332] The test results are summarized in Table 4.
[0333] Table 4
[0334] Powder mixture 1 125-180 + / - + / - + / - Powder mixture 2 Approximately 500 - + / - -
[0335] Powder mixture 1 can be easily applied using a bellows application device. However, powder mixture 2 is difficult to apply because the powder particles are very fluffy. To allow for comparability of sealing, hemostatic, and wetting properties, powder mixture 2 was applied using a tube in this experiment.
[0336] Example 5
[0337] Five different powder mixtures were prepared by method C1 using powders obtained by method A2 (EL-POX:sugar = 1:1 w / w) and five different powders obtained by method B1. Trehalose was used as the sugar component in all powders.
[0338] The only difference between these five different powder mixtures is that the powders obtained by method B1 contain different amounts of trehalose:
[0339] Powder mixture 1 2:8:8 Powder mixture 2 2:8:2 Powder mixture 3 2:8:4 Powder mixture 4 2:8:12 Powder mixture 5 2:8:16
[0340] The sealing and hemostatic properties of the two powders (heparinized) were tested in an in vitro porcine liver system. The powders were applied in 0.5 g amounts using a bellows applicator.
[0341] The test results are summarized in Table 5.
[0342] Table 5
[0343] Powder mixture 1 125-180 + + + Powder mixture 2 125-180 - + / - - Powder mixture 3 125-180 + / - + - / + Powder mixture 4 125-180 + / - + + Powder mixture 5 125-180 + / - + / - +
[0344] Powder mixtures 1, 3, 4, and 5 can be easily applied using a corrugated applicator. Powder mixture 2 is less easy to apply because the particles are quite fluffy.
[0345] Example 6
[0346] Three different powder mixtures were prepared by method C1 using the powder obtained by method A2 (EL-POX:sugar = 1:1 w / w) and three different powders obtained by method B1. The three different powders obtained by method B1 differed only in the type of sugar used. In all cases, NU-POX, gelatin sponge, and sugar were present in the powder from method B in a weight ratio of 2:8:8.
[0347] Powder mixture 1 Trehalose Powder mixture 2 Mannitol Powder mixture 3 Glucan 40
[0348] The sealing and hemostatic properties of the two powders (heparinized) were tested in an in vitro porcine liver system. The powders were applied in doses of 0.5 g.
[0349] The test results are summarized in Table 6.
[0350] Table 6
[0351] Powder mixture 1 125-180 + + + Powder mixture 2 125-180 + + + Powder mixture 3 125-180 + / - + +
[0352] Example 7
[0353] Four different powder mixtures were prepared by method C1 using the powder obtained by method A2 (EL-POX:sugar = 1:1 w / w), one powder was obtained by method B1, and three different powders were obtained by method B2. The three different powders obtained by method B2 differed in the amount of surfactant (Pluronic F-127) used. Trehalose was used as the sugar component in all powders.
[0354] Powder mixture 1 0 Powder mixture 2 0.1 Powder mixture 3 1.0 Powder mixture 4 3.0
[0355] The sealing and hemostatic properties of the two powders (heparinized) were tested in an in vitro porcine liver system. The powders were applied in doses of 0.5 g.
[0356] The test results are summarized in Table 7.
[0357] Table 7
[0358] Powder mixture 1 63-125 + + + Powder mixture 2 63-125 ++ ++ ++ Powder mixture 3 63-125 ++ ++ ++ Powder mixture 4 63-125 ++ ++ ++
[0359] Example 8
[0360] Example 7 was repeated, except that sodium dodecyl sulfate (SDS) was used as the surfactant this time.
[0361] Powder mixture 1 0 Powder mixture 2 0.1 Powder mixture 3 1.0 Powder mixture 4 3.0
[0362] The sealing and hemostatic properties of the two powders (heparinized) were tested in an in vitro porcine liver system. The powders were applied in doses of 0.5 g.
[0363] The results are summarized in Table 8.
[0364] Table 8
[0365] Powder mixture 1 63-125 + + + Powder mixture 2 63-125 ++ ++ ++ Powder mixture 3 63-125 ++ ++ ++ Powder mixture 4 63-125 ++ ++ ++
[0366] Example 9
[0367] Example 7 was repeated, except that this time poloxamer P-188 was used as the surfactant.
[0368] Powder mixture 1 0 Powder mixture 2 0.1 Powder mixture 3 1.0 Powder mixture 4 3.0
[0369] The sealing and hemostatic properties of the two powders (heparinized) were tested in an in vitro porcine liver system. The powders were applied in doses of 0.5 g.
[0370] The test results are summarized in Table 9.
[0371] Table 9
[0372] Powder mixture 1 63-125 + + + Powder mixture 2 63-125 ++ ++ ++ Powder mixture 3 63-125 ++ ++ ++ Powder mixture 4 63-125 ++ ++ ++
[0373] Example 10
[0374] Three different powder mixtures were prepared by method C1 using one powder (EL-POX:sugar = 1:1 w / w) obtained by method A2 and three different powders obtained by method B1. The three powders obtained by method B2 differed in that they contained different types of gelatin sponge.
[0375] Powder mixture 1 <![CDATA[GELITA-SPON powder 1 > Powder mixture 2 <![CDATA[Cutanplast Powder 2 <!-- 23 -->]]> Powder mixture 3 <![CDATA[Surgispon powder 3 >
[0376] 1 Gelita Medical AG, Germany
[0377] 2 Mascia Brunelli Spa, Italy
[0378] 3 Aegis Lifesciences PVT Ltd,India
[0379] The sealing and hemostatic properties of these sealing powders were tested in an in vitro porcine liver system (heparinized). The powder was applied in doses of 1.0 g.
[0380] The test results are summarized in Table 10.
[0381] Table 10
[0382] Powder mixture 1 63-125 + + + Powder mixture 2 63-125 + + + Powder mixture 3 63-125 + + +
[0383] Example 11
[0384] Different powder mixtures were prepared by method C1 using powders obtained by method A2 (EL-POX:sugar = 1:1 w / w) and powders obtained by method B1. Trehalose was used as the sugar component in all powders. The particle size of the powders varied as shown in Table 11.
[0385] The sealing and hemostatic properties of these sealing powders were tested in an in vitro porcine liver system (heparinized). The powder was applied in doses of 0.5 g.
[0386] The test results are summarized in Table 11.
[0387] Table 11
[0388] Powder mixture 1 63-125 + + + Powder mixture 2 125-250 + + + Powder mixture 3 250-500 - - + Powder mixture 4 63-90 + + + Powder mixture 5 90-125 ++ ++ + Powder mixture 6 125-180 ++ ++ + Powder Mixture 7 180-250 + +- +
[0389] Example 12
[0390] Different powder mixtures are prepared using powders obtained by method A1 or A2 (EL-POX:sugar = 1:1 w / w) and powders obtained by method B2, by powder mixing method C1 or C2 or by granulation method C3.
[0391] Powder mixture 1 Method A1 Method B2 Method C2 Powder mixture 2 Method A2 Method B2 Method C1 Powder mixture 3 Method A2 Method B2 Method C3
[0392] In all powders, trehalose is used as the sugar component.
[0393] The sealing and hemostatic properties of the two powders (heparinized) were tested in an in vitro porcine liver system. The powders were applied in doses of 0.5 g.
[0394] The test results are summarized in Table 12.
[0395] Table 12
[0396] Powder mixture 1 <63 + + / - + Powder mixture 2 125-180 ++ ++ + Particle 3 125-180 +++ +++ +
[0397] Example 13
[0398] In vivo studies were conducted on porcine spleens using a mixture (0.5 g) of powders prepared by method C1 from powders obtained by method A2 (EL-POX:sugar = 1:1 w / w) and powders obtained by method B1. Trehalose was used as the sugar component in all powders. The powders differed only in particle size. The test results are summarized in Table 13.
[0399] Table 13
[0400] Powder mixture 1 90-125 + + + Powder mixture 2 125-180 ++ + +
[0401] Example 14
[0402] The performance of the powder mixture of Example 12 was also evaluated in an in vivo spleen test using 0.5 g of the powder mixture. The results are shown in Table 14.
[0403] Table 14
[0404] Powder mixture 1 90-125 + + + Powder mixture 2 125-180 ++ + +
[0405] Example 15
[0406] In vitro tests were conducted on heparinized porcine livers with abrasions (3 cm × 3 cm). The sealed powder (1 g) used was prepared by either dry mixing method C1 (powder mixture 1) or granulation method C3 (particles 2). In both cases, powders obtained by method A2 and method B2 were used. The powders were applied using a corrugated applicator. Trehalose was used as the sugar component in all powders.
[0407] The test results are summarized in Table 15.
[0408] Table 15
[0409] Powder mixture 1 125-180 ++ ++ + Particle 2 125-180 +++ ++ +
[0410] Example 16
[0411] The sealing properties of the sealing powder in the absence of blood were evaluated in the extracorporeal ventilation lung model described above. The pressure at which leakage began was recorded after the application of the sealing powder.
[0412] The sealed powder for testing is obtained by dry mixing (method C1) and granulation (method C3) of powders containing NHS-POx and powders containing NU-POx. The powder containing NHS-POx consists solely of NHS-POx, or it is granules of NHS-POx and trehalose obtained by method A2. The powder containing NU-POx is granules further containing gelatin sponge and trehalose and obtained by method B1 or B2.
[0413] The test results are summarized in Table 16.
[0414] Table 16
[0415]
[0416] 1 Pluronic F-177
[0417] Example 17
[0418] Granulation was performed using powder obtained by method A2 (EL-POX:trehalose = 1:1 w / w) and powder obtained by method B2 (granules containing NU-POx), the difference being that in each case the gelatin sponge in the latter powder was replaced by another water-insoluble polymer containing reactive nucleophilic groups as shown below:
[0419] Particle 1 <![CDATA[Deacetylated chitosan 1 > Particle 2 <![CDATA[Reduced cross-linked gelatin 2 >
[0420] Purchased from Sigma Aldrich, MW 100,000-300,000, deacetylation grade 85%.
[0421] 2. Prepared by the method described in WO 2021 / 009014 (page 29, lines 3 to 14).
[0422] The sealing and hemostatic properties (heparinized) of these two granules were tested in an in vitro porcine liver system. The granules were administered in doses of 0.5 g. Tests were performed in duplicate. The results are summarized in Table 17.
[0423] Table 17
[0424] Particle 1 ++ ++ + Particle 2 ++ ++ +
[0425] Comparative Example B
[0426] Granulation was performed using powder obtained by method A2 (EL-POX:trehalose = 1:1 w / w) and powder obtained by method B2 (granules containing NU-POX), the difference being that in this case, the gelatin sponge was oxidized into absorbable cellulose ( Purchased from Gelita Medical GmbH) as a substitute.
[0427] The sealing and hemostatic properties (heparinized) of these particles were tested in an in vitro porcine liver system. The particles were administered in doses of 0.5 g. Tests were performed in duplicate. The results are summarized in Table 18.
[0428] Table 18
[0429] Particles - - -
[0430] Example 18
[0431] Granulation was performed using powder obtained by method A2 (EL-POX:sugar = 1:1 w / w) and powder obtained by method B2 (granules containing NU-POX), except that in this case, trehalose in the first powder was replaced by mannitol.
[0432] The sealing and hemostatic properties (heparinized) of these particles were tested in an in vitro porcine liver system. The particles were administered in doses of 0.5 g. Tests were performed in duplicate. The results are summarized in Table 19.
[0433] Table 19
[0434] Particles ++ ++ +
[0435] Example 19
[0436] Granulation was performed using granulation method C3, using powder obtained by method A2 (EL-POX:sugar = 1:1 w / w) and powder obtained by method B2, the difference being that 8-arm polyethylene glycol (8-arm PEG-NH, purchased from Creative PEGWorks) carrying 8 amine groups was used instead of NU-POx in the latter powder.
[0437] The sealing and hemostatic properties (heparinized) of these granules were tested in an in vitro porcine liver system. Granules were administered in doses of 0.5 g. Tests were performed in duplicate. The results are summarized in Table 20.
[0438] Table 20
[0439] Particles + + +
Claims
1. A bioabsorbable sealing powder, comprising: (a) At least 5% by weight of a water-soluble electrophilic polymer carrying at least 3 reactive electrophilic groups, wherein the reactive electrophilic groups are capable of reacting with amine groups to form covalent bonds; (b) 1% to 50% by weight of a water-soluble nucleophilic crosslinking agent carrying at least two reactive nucleophilic groups, wherein the reactive nucleophilic groups are capable of reacting with the reactive electrophilic groups of the electrophilic polymer in the presence of water to form a covalent bond between the electrophilic polymer and the nucleophilic crosslinking agent; (c) 1% to 60% by weight of absorbent particles, wherein the absorbent particles contain at least 50% by weight of a water-insoluble polymer, wherein the water-insoluble polymer contains a reactive nucleophilic group selected from amine groups, thiol groups and combinations thereof. (d) 10% to 75% by weight of a water-soluble dispersant that is a solid at 20°C, wherein the water-soluble dispersant is selected from monosaccharides, disaccharides, oligosaccharides, sugar alcohols, and combinations thereof; The combination of components (a), (b), (c) and (d) constitutes at least 60% by weight of the sealing powder. The sealing powder has a tap density in the range of 0.3 g / ml to 0.9 g / ml; At least 90% by weight of the powder has a diameter of less than 600 µm, and no more than 10% by weight of the powder has a diameter of less than 10 µm; wherein the sealing powder has a volume-weighted average diameter (D [4,3]) in the range of 65 µm to 250 µm; and The powder contains at least 50% by weight of particles in the form of agglomerates containing each of components (a), (b), (c) and (d), consisting of subparticles A containing only components (a) and (d) and subparticles B containing only components (b), (c) and (d).
2. The powder according to claim 1, wherein, The electrophilic polymer is selected from electrophilic polyoxazoline, electrophilic polyethylene glycol, and combinations thereof.
3. The powder according to claim 1 or 2, wherein, The nucleophilic crosslinking agent is selected from nucleophilic polyoxazoline, nucleophilic polyethylene glycol, polyethyleneimine, and combinations thereof.
4. The powder according to claim 1 or 2, wherein, The water-insoluble polymer containing reactive nucleophilic groups is selected from proteins, deacetylated chitosans, and combinations thereof.
5. The powder according to claim 1 or 2, wherein, The ratio between the total number of reactive electrophilic groups provided by the electrophilic polymer and the total number of reactive nucleophilic groups provided by the nucleophilic crosslinker is in the range of 1:0.05 to 1:0.
4.
6. The powder according to claim 1 or 2, wherein, The powder comprises 20% to 80% by weight of subparticles A containing only components (a) and (d) and 20% to 80% by weight of subparticles B containing only components (b), (c) and (d).
7. The powder according to claim 6, wherein, The subparticles A containing only components (a) and (d) and the subparticles B containing only components (b), (c) and (d) together constitute at least 60% by weight of the sealing powder.
8. The powder according to claim 1 or 2, wherein, The powder contains at least 60% by weight of particles containing each of components (a), (b), (c) and (d).
9. The powder according to claim 1 or 2, wherein, The water-soluble dispersant is selected from sucrose, trehalose, lactose, maltitol, mannitol, sorbitol, xylitol, cyclodextrin, maltodextrin, dextran, and combinations thereof.
10. The powder according to claim 1 or 2, wherein, The water-soluble dispersant is selected from sucrose, trehalose, mannitol, and combinations thereof.
11. A method for preparing a bioabsorbable sealing powder according to any one of claims 1 to 10, comprising the following steps: (a) Providing subparticles A containing only the electrophilic polymer and the water-soluble dispersant; (b) Providing subparticles B containing only the nucleophilic crosslinking agent, the water-absorbing particles, and the water-soluble dispersant; (c) Combine the subparticle A and the subparticle B.
12. The method according to claim 11, wherein, The subparticles A and B are combined into an agglomerate.
13. An apparatus for applying sealing powder, comprising: ● A reservoir for containing the bioabsorbable sealed powder according to any one of claims 1 to 10; ● An elongated hollow tubular structure having a proximal end and a distal end, the distal end having a powder outlet, and the proximal end being connected to the reservoir; ● A manual air pump, which is arranged to generate an airflow that transports powder from the reservoir through the elongated hollow tubular structure and through the powder outlet.
14. A biocompatible flexible hemostatic sheet, comprising: ● Cohesive fiber carrier structure containing three-dimensional interconnected gap space; and ● Bioabsorbable sealing powder according to any one of claims 1 to 10; The sealing powder is distributed within the gap space and / or fixed to the fiber carrier structure.
15. A kit for preparing a bioabsorbable sealed suspension, comprising: ● A first container or compartment containing a biocompatible liquid; and ● A second container or compartment containing the bioabsorbable sealing powder according to any one of claims 1 to 10.
16. A bioabsorbable sealed suspension, comprising: ● Biocompatible continuous liquid non-aqueous phase; and ● A dispersion phase comprising the bioabsorbable sealing powder according to any one of claims 1 to 10.
Citation Information
Patent Citations
Dry hemostatic compositions and methods for their preparation
US20030064109A1
Process for making dry and stable hemostatic compositions
US20120021058A1
Oxidized regenerated cellulose hemostatic powders and methods of making
US20130316974A1
Biodegradable non-woven material for medical purposes
US20150010612A1
Hemostatic compositions
US20160271228A1